Combined robot motor assistance with neural circuit-based virtual reality (NeuCir-VR) lower extremity rehabilitation training in patients after stroke: a study protocol for a single-centre randomised controlled trial - Meng Ren; Xu-Yun Hua; Jia-Jia Wu; Jian-Guang Xu; Zhi-Qing Zhou; Jing-Jing Xu; Chun-Lei Shan (BMJ Open, 2022)
Introduction Improving lower extremity motor function is the focus and difficulty of post-stroke rehabilitation treatment. More recently, robot-assisted and virtual reality (VR) training are commonly used in post-stroke rehabilitation and are considered feasible treatment methods. Here, we developed a rehabilitation system combining robot motor assistance with neural circuit-based VR (NeuCir-VR) rehabilitation programme involving procedural lower extremity rehabilitation with reward mechanisms, from muscle strength training, posture control and balance training to simple and complex ground walking training. The study aims to explore the effectiveness and neurological mechanisms of combining robot motor assistance and NeuCir-VR lower extremity rehabilitation training in patients after stroke.Methods and analysis This is a single-centre, observer-blinded, randomised controlled trial. 40 patients with lower extremity hemiparesis after stroke will be recruited and randomly divided into a control group (combined robot assistance and VR training) and an intervention group (combined robot assistance and NeuCir-VR training) by the ratio of 1:1. Each group will receive five 30 min sessions per week for 4 weeks. The primary outcome will be Fugl-Meyer assessment of the lower extremity. Secondary outcomes will include Berg Balance Scale, Modified Ashworth Scale and functional connectivity measured by resting-state functional MRI. Outcomes will be measured at baseline (T0), post-intervention (T1) and follow-ups (T2–T4).Ethics, registration and dissemination The trial was approved by the Ethics Committee of Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Chinese Traditional Medicine (Grant No. 2019–014). The results will be submitted to a peer-reviewed journal or at a conference.Trial registration number ChiCTR2100052133.